A Nested Case-Control Study of the Relationship between Salivary Inflammatory Mediators, Periodontal Parameters, and Preterm Birth in a Chinese Population. (18th August 2022) - Wu, Min; Ye, Chanjuan; Li, Huijun; Yang, Xiuqiao; Zhu, Sujun; Zhou, Fangming; Hao, Ying; Chen, Shaowu; Jiang, Shaoyun
Abstract : Background . To explore whether salivary inflammatory mediators and periodontal indices at different gestational stages can be taken as indicators of preterm birth (PTB). Methods . This nested case-control study enrolled systemically healthy pregnant women at 9 to 36 weeks of gestation. Periodontal indices were measured at the enrollment date, and interleukin-1 β (IL-1 β ), IL-6, tumor necrosis factor (TNF- α ), prostaglandin E2 (PGE2), and 8-hydroxy-deoxyguanosine (8-OHdG) in the saliva were determined by enzyme-linked immunosorbent assay (ELISA). The birth outcome was recorded. Results . PTB occurred in 26 women. A total of 104 matched women with full-term birth (FTB) were used as controls. The PTB women enrolled at 24-28 gestational weeks displayed a significantly greater bleeding index (BI), probing pocket depth (PD), PD ≥ 4 mm sites (%), saliva-TNF- α, and saliva-PGE2 (P < 0.05 ). BI and PGE2 in the saliva were found to be positively associated with PTB (OR = 4.79, P = 0.048, 95 % CI = 1.014 to 22.628 ; OR = 1.07, P = 0.04, 95 % CI = 1.004 to 1.135, respectively). The areas under the receiver operating characteristic curve (ROC) of BI and saliva-PGE2 were 0.82 and 0.78, respectively, and that of the combined detection was 0.91, which was larger than either marker alone, although the differences were not significant (P > 0.05 ). Conclusions . The combination of BI and PGE2 in saliva at 24-28 gestational weeks could be a predictor of PTB in asymptomatic women. However, the results should be further explored with larger sample size.